Probiotics supplementation for management of type II diabetes risk factors in adults with polycystic ovarian syndrome: a meta-analysis of randomized clinical trial - Chengcheng Zhang; Yingyue Sheng; Jinchi Jiang; Yuzheng Xue; Leilei Yu; Fengwei Tian; Jianxin Zhao; Hao Zhang; Jian Jin; Qixiao Zhai (Food Science and Human Wellness)
This meta-analysis of randomized controlled trials aimed to evaluate the effects of probiotic supplementation on glucose homeostasis in patients with polycystic ovary syndrome (PCOS). The meta-analysis was performed in accordance with the Cochrane Handbook guidelines and relevant the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement criteria. Of 825 identified reports, 11 randomized clinical trials were included in the meta-analysis. An analysis of pooled extracted data revealed that supplementation with probiotics significantly decreased fasting blood glucose (FBG, n = 7; standardized mean difference (SMD) = −0.40; 95 % confidence interval (CI): −2.02, −0.02; P = 0.04) and insulin levels (n = 6; SMD = −0.57; 95 % CI: −0.89, −0.25; P = 0.0004) and the homeostatic model assessment of insulin resistance (n = 7; SMD = −0.64; 95 % CI: −0.96, −0.31; P = 0.0001) while increasing the quantitative insulin sensitivity check index (QUICKI, n = 5; SMD = 0.58; 95 % CI: 0.08, 1.09; P = 0.02) in patients with PCOS. The FBG-reducing effect decreased as the baseline body mass index (BMI) and mean age of the participants increased. Indeed, a greater number of bacterial species and a higher bacterial dose were shown to reduce QUICKI effectively. The systematic review indicated that probiotic supplementation may help to control glucose homeostasis in adults with polycystic ovarian syndrome.